PENGARUH SUMBER PENDANAAN DAN KEPUTUSAN INVESTASI PADA NILAI PERUSAHAAN SEKTOR PROPERTI PADA BURSA EFEK INDONESIA - Utamayasa, I Made Arya Karang; Suputra, I D.G Dharma (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Maximize the value of the company is effectively done by continuing to implement the business development in order to anticipate the current fierce competition increasingly keen to be always carried out by the company and will never be separated from the availability of funds, which amount will be adjusted by the amount of investment to be financed. The influence of internal and external sources of funding to the value of the company and the impact of investment decisions on the value of the company is the purpose of this study. Explanatory research is the method of this study. The data used in this study is a property company's financial statements from 2007 to 2013. The data in this study were obtained through the method of documentation or have been provided by the company. The analysis of the data used is the classical assumption test, regression analysis and coefficient of determination. Based on the survey results revealed that the source of funding internal, external funding and investment decisions are positive and significant impact on the value of the property sector companies listed on the Indonesia Stock Exchange.
Keywords: Sources of Financing, Investment, Corporate Values